If not us, then who? - On the repatriation of Swedish women and children from the al Hol and al Roj camps in the Syrian Arab Republic - Volgsten,Aylin (2021)
In the al Hol and al Roj camps in the north-eastern parts of the Syrian Arab Republic, women and children allegedly affiliated with the terrorist group the Islamic State of Iraq and the Levant are detained in precarious humanitarian and security conditions that have been equated with torture or cruel, inhuman or degrading treatment or punishment by the United Nations. In early 2021, the United Nations called upon states to repatriate their nationals from the camps. Sweden has refused to do so, arguing that it has no legal obligation to repatriate the 50 Swedish women and children detained in the camps. This thesis examines the extent of Sweden’s legal obligations under international human rights law and within the area of counter-terrorism and asks whether Sweden has to repatriate its nationals from the al Hol and al Roj camps in order to fulfil these obligations. To answer this question, the thesis examines and analyses the scope of positive obligations stemming from the prohibition of torture or cruel, inhuman or degrading treatment or punishment and the concept of extraterritorial jurisdiction under international human rights law under three core human rights treaties, namely the International Covenant on Civil and Political Rights, the European Convention on Human Rights and the Convention on the Rights of the Child. Based on these findings, it argues for a universalist approach to extraterritorial jurisdiction and an extensive reading of positive human rights obligations in this specific case. The thesis also examines and analyses Sweden’s obligation to bring suspected terrorists to justice, stemming from relevant counter-terrorism frameworks established by the United Nations and the Council of Europe from a human security perspective. This thesis concludes that Sweden must repatriate its nationals from the al Hol and al Roj camps to fulfil its international human rights and counter-terrorism obligation in this specific case. Failing to do so not only undermines individual and thus national and international security, but also Sweden’s legitimacy as a rule of law and human rights-abiding actor.
Keywords: public international law; international human rights law; repatriation; jurisdiction; terrorism; counter-terrorism; Syria; ISIL